Similar Clinical and Surgical Outcomes Achieved with Early Compared to Late Anti-TNF Induction in Mild-to-Moderate Ulcerative Colitis: A Retrospective Cohort Study - Christopher Ma; Candace L. Beilman; Vivian W. Huang; Darryl K. Fedorak; Karen Wong; Karen I. Kroeker; Levinus A. Dieleman; Brendan P. Halloran; Richard N. Fedorak (Canadian Journal of Gastroenterology and Hepatology)
Background. Biologic agents targeting tumor necrosis factor alpha are effective in the management of ulcerative colitis (UC), but their use is often postponed until after failure of other treatment modalities. Objectives. We aim to determine if earlier treatment with infliximab or adalimumab alters clinical and surgical outcomes in UC patients. Methods. A retrospective cohort study was conducted evaluating UC outpatients treated with infliximab or adalimumab from 2003 to 2014. Patients were stratified by time to first anti-TNF exposure; early initiation was defined as starting treatment within three years of diagnosis. Primary outcomes were colectomy, UC-related hospitalization, and clinical secondary loss of response. Kaplan-Meier analysis was used to assess time to the primary outcomes. Results. 115 patients were included (78 infliximab, 37 adalimumab). Median follow-up was 175.6 weeks (IQR 72.4–228.4 weeks). Fifty-seven (49.6%) patients received early anti-TNF therapy; median time to treatment in this group was 38.1 (23.3–91.0) weeks compared to 414.0 (254.0–561.3) weeks in the late initiator cohort (p<0.0001). Patients treated with early anti-TNF therapy had more severe endoscopic disease at induction (mean Mayo endoscopy subscore 2.46 (SD ± 0.66) versus 1.86 (±0.67), p<0.001) and trended towards increased risk of colectomy (17.5% versus 8.6%, p=0.16) and UC-related hospitalization (43.9% versus 27.6%, p=0.07). In multivariate regression analysis, early anti-TNF induction was not associated with colectomy (HR 2.02 [95% CI: 0.57–7.20]), hospitalization (HR 1.66 [0.84–3.30]), or secondary loss of response (HR 0.86 [0.52–1.42]). Conclusions. Anti-TNF therapy is initiated earlier in patients with severe UC but earlier treatment does not prevent hospitalization, colectomy, or secondary loss of response.